2022
DOI: 10.36262/widyakala.v9i2.572
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Financial Target, Ineffective Monitoring, Pergantian Auditor, dan Perubahan Direksi Terhadap Kecurangan Laporan Keuangan

Abstract: This study aims to determine the effect of financial target, ineffective monitoring, auditors change, and directors change on financial statement fraud which is proxied by earnings management. The proxied of each variable are return on asset (ROA), ratio of independent board of commissioners, and dummy variables for auditor change and director change. The data is secondary data. The population is manufacturing companies sector consumer goods industry listed on Indonesia Stock Exchange (IDX) for the period 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
4

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
1
0
4
Order By: Relevance
“…Tuntutan ini dapat membuat manajer merasa tertekan. Tingginya target ROA yang ditargetkan perusahaan kepada manajemen berbanding lurus dengan tingginya peluang perusahaan melakukan tindakan kecurangan laporan keuangan Putri & Qintharah (2023), Ghaisani & Supatmi (2023), Azizah et al (2022), (Jao et al, 2020). Penelitian dari Nurhafifa et al (2023) menyatakan hal lain, tinggi rendahnya tingkat ROA tidak menyebabkan perusahaan membuat akun penipuan karena menurutnya manajemen berkeyakinan target ROA mudah dicapai.…”
Section: Pendahuluanunclassified
See 3 more Smart Citations
“…Tuntutan ini dapat membuat manajer merasa tertekan. Tingginya target ROA yang ditargetkan perusahaan kepada manajemen berbanding lurus dengan tingginya peluang perusahaan melakukan tindakan kecurangan laporan keuangan Putri & Qintharah (2023), Ghaisani & Supatmi (2023), Azizah et al (2022), (Jao et al, 2020). Penelitian dari Nurhafifa et al (2023) menyatakan hal lain, tinggi rendahnya tingkat ROA tidak menyebabkan perusahaan membuat akun penipuan karena menurutnya manajemen berkeyakinan target ROA mudah dicapai.…”
Section: Pendahuluanunclassified
“…Semakin kecil rasio dewan komisaris membuat perusahaan mengalami ketidakefektifan pengawasan kinerja, sehingga dapat membuat praktik kecurangan laporan keuangan semakin tinggi Ghaisani & Supatmi (2023), (Putri & Qintharah, 2023). Penelitian lain menunjukkan bahwa dewan komisaris dalam sebuah perusahaan yang berasal dari pihak eksternal juga belum tentu dapat membuat efektivitas pengawasan manajemen mencegah terjadinya kecurangan laporan keuangan meningkat (Azizah et al, 2022).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…One of them is the case of PT Envy Technologies Indonesia Tbk (ENVY) in 2019, where the alleged manipulation of financial statements was revealed in ENVY's management letter to the Indonesia Stock Exchange (IDX), which explained the problems related to the financial statements of PT Ritel Global Solusi (RGS). Another case was in 2016 at PT Hanson International Tbk (MYRX), where there were allegations of manipulation related to the recognition of land plot sales revenue worth Rp.732 billion which resulted in overstated December 2016 financial statements of Rp 613 billion, and led to sanctions against the managing director by the Financial Services Utami et al (2022), Wilestari & Fujiana (2021) found an effect, while Rosa Sanjayyana & Urumsah (2021), Setiawan & Trisnawati (2022) concluded that there was no significant effect.…”
Section: Introductionmentioning
confidence: 99%